Simplex Society How to Humanize - Stroeken, Koen (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
This open access book provides thought-provoking anthropology grounded in comparative ethnography. The theory captures the current historical moment, the long-term trends that led us here, and the prospects for a humane future. The experience of complexity characterizing a globalized information society triggers simplexes. These unidimensional responses instrumental in bringing about a predictable effect are altering our ways of communicating and the technologies we design. In Part I, a 'speciated' history, injected with the anthropology of Bateson and Gluckman, describes the semantic and experiential impoverishment of the lifeworld. After going through the affects of distrust (the neolithic lifeway), of futility (industrial lifeway) and disconnection (post-knowledge), the human species today depends for its survival on installing a new lifeway, which manages to wed (eco-social) inclusion to the already difficult first pair of the French Revolution. The species needs to rehumanize. Part II illustrates the remedies currently developed: to reframe, re-sphere and re-source. What do critical street art, international football matches, presidential elections, hip-hop dissing performances, charismatic church services, intuition stimulation, and 'pre-ceptive' experiences of consciousness have in common? They are moments of the real. Rooted in 'life sensing', they are tensors organizing frameshift. As multiplex measures tackling the simplex, these tensors overcome the cultural relativism of the postmodern matrix.